The Impact of Social Rejection on Anxiety Symptoms in Adolescents: The Mediating Role of Loneliness and Mindfulness - Kavoosi, Nikta; Bakhtiari Saeid, Farima; Vafapour , Parisa (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to investigate the impact of social rejection on anxiety symptoms in adolescents, with the mediating roles of loneliness and mindfulness. Methods and Materials: A descriptive correlational design was employed involving 400 adolescent students (aged 13–18) in Tehran, selected using multistage cluster sampling. Standardized instruments were used to assess social rejection, loneliness, mindfulness, and anxiety symptoms. Data were analyzed using Pearson correlation (SPSS-27) and Structural Equation Modeling (AMOS-21). Model fit was evaluated using multiple fit indices, and the assumptions of normality, linearity, and multicollinearity were verified prior to analysis. Findings: Results revealed significant positive correlations between social rejection and both anxiety symptoms (r = .63, p < .001) and loneliness (r = .57, p < .001), while mindfulness was negatively correlated with both variables (p < .001). Structural equation modeling demonstrated that social rejection significantly predicted anxiety symptoms directly (β = 0.36, p < .001), and indirectly through loneliness (β = 0.13, p < .001) and mindfulness (β = 0.09, p < .001). The total effect of social rejection on anxiety was substantial (β = 0.58, p < .001). The model fit indices indicated a good fit (χ²/df = 1.94, CFI = 0.96, TLI = 0.95, RMSEA = 0.048). Conclusion: The findings highlight that social rejection significantly contributes to adolescent anxiety symptoms, both directly and indirectly through increased loneliness and reduced mindfulness. These results emphasize the importance of addressing peer-related social stress and enhancing protective psychological resources such as mindfulness to mitigate anxiety in adolescents. The study contributes to a deeper understanding of the psychosocial mechanisms underlying adolescent mental health and offers practical implications for school-based prevention programs.